STRATEGI PEMERINTAH KOTA TASIKMALAYA DALAM MENERAPKAN TEKNOLOGI INFORMASI PEMERINTAHAN UNTUK MENINGKATKAN TATA KELOLA PEMERINTAHAN - Ikhbaluddin, Ikhbaluddin (Jurnal Teknologi dan Komunikasi Pemerintahan, 2020)
The use of technology of information in the government sector well known as TIP (Technology of Government Information) it was not a new concerning formally, Indonesia just had the regulation on the 2003, refer to ordinance the 2003 number 3 that consist on development of electronic government. The regulation has 6 (six) strategies and phases of TIP development comprehensively. However, Tasikmalaya City Government still faces many problems in it’s implementation. Related with this research, it capable of proof that there are several obstacles in the implementation of TIP in Tasikmalaya City Government, such as either regional regulation or Mayor Regulation Governing Regulated the implementation of TIP in a comprehensive manner TIP application have been built are still partial in each Organization of Local Government (OPD), and have not been integrated in an interoperability system. The lack of human resources who have competence in this sector, and it’s implementation does not involve to another such as the people and private parties. Based on the conditions above it will impact on the weakness of government implementation, especially on public service as a good governance indicator should be have. The key word : Technology of Government Information (E-Government)